Post‐synthetic 'Click' Synthesis of RAFT Polymers with Pendant Self‐immolative Triazoles. Issue 4 (22nd January 2021) - Forder, Timothy N.; Maschmeyer, Peter G.; Zeng, Haoxiang; Roberts, Derrick A.
Abstract: Self‐immolative linkers offer efficient mechanisms for deprotecting 'caged' functional groups in response to specific stimuli. Herein we describe a convenient 'click' chemistry method for introducing pendant self‐immolative linkers to a polymer backbone through post‐polymerization modification. The introduced triazole rings serve both to anchor the stimuli‐cleavable trigger groups to the polymer backbone, while also forming a functional part of the self‐immolation cascade. We investigate the polymerization kinetics, post‐synthetic modification, and self‐immolation mechanism of a model polymer system, and discuss avenues for future studies on poly‐pendant self‐immolative triazoles as a modular, stimuli‐responsive macromolecule platform. Abstract : Click and cleave : Triazole‐based self‐immolative linkers can be introduced as pendant groups onto RAFT polymers via 'click' chemistry. Using a model system, we investigate the polymerization kinetics of an alkyne‐pendant precursor, its post‐synthetic modification via the CuAAC reaction and self‐immolation kinetics, which showed rapid and efficient uncaging of amine groups on the polymer following the self‐immolation cascade.